A High-Density Linkage Map Reveals Sexual Dimorphism in Recombination Landscapes in Red Deer (Cervus elaphus). Issue 8 (1st August 2017) - Johnston, Susan E; Huisman, Jisca; Ellis, Philip A; Pemberton, Josephine M
Abstract: High-density linkage maps are an important tool to gain insight into the genetic architecture of traits of evolutionary and economic interest, and provide a resource to characterize variation in recombination landscapes. Here, we used information from the cattle genome and the 50 K Cervine Illumina BeadChip to inform and refine a high-density linkage map in a wild population of red deer ( Cervus elaphus ). We constructed a predicted linkage map of 38, 038 SNPs and a skeleton map of 10, 835 SNPs across 34 linkage groups. We identified several chromosomal rearrangements in the deer lineage relative to sheep and cattle, including six chromosome fissions, one fusion, and two large inversions. Otherwise, our findings showed strong concordance with map orders in the cattle genome. The sex-averaged linkage map length was 2739.7 cM and the genome-wide autosomal recombination rate was 1.04 cM/Mb. The female autosomal map length was 1.21 longer than that of males (2767.4 cM vs. 2280.8 cM, respectively). Sex differences in map length were driven by high female recombination rates in peri-centromeric regions, a pattern that is unusual relative to other mammal species. This effect was more pronounced in fission chromosomes that would have had to produce new centromeres. We propose two hypotheses to explain this effect: (1) that this mechanism may have evolved to counteract centromeric drive associated with meiotic asymmetry in oocyte production; and/or (2) that sequence and structural characteristics suppressing recombination in close proximity to the centromere may not have evolved at neo-centromeres. Our study provides insight into how recombination landscapes vary and evolve in mammals, and will provide a valuable resource for studies of evolution, genetic improvement, and population management in red deer and related species.